VARIASI TEMPORAL MAKANAN IKAN SEPAT LAYANG (Trichogaster leerii, Blkr. 1852) DI HUTAN RAWA GAMBUT DESA DADAHUP, KALIMANTAN TENGAH - Ahmad Zahid; MF. Rahardjo; Sutrisno Sukimin; Lenny S. Syafei (The East Java Biological Society, 2009)
Changes in habitat quality and resource availability associated with seasonal variation in hydrology strongly influences ecological interactions. The study was conducted from July to December 2007 which aiming to described prey item of Trichogaster leerii in peatswamp forest district of Dadahup, Central Kalimantan based on temporal variation (low and high water period). Each month, research zone, and size classes; the stomach contents on consisted predominantly of periphyton, such as Diatoma; Fragillaria; Nitzschia; Navicula; and Tabellaria. Diatoma was the dominance in the stomach contents and prey-selectively ingested of T. leerii. Size classes-based, the diet of T. leerii was least similar during falling and rising water. Feeding strategy of T. leerii was generalized. No different of diet breadth during the low- and the high-water period. Diet overlap between pairs of size classes of T. leerii was high in low- and high water period.